Interception of solar radiation by the productive structures of spring canola hybrids - Fochesatto,Elizandro (2016)
ABSTRACT: The objective of this study was to adjust parameters related to the interception of photosynthetically active radiation (PAR) by reproductive structures of spring canola, with different nitrogen levels and hybrids. Two field experiments were conducted, being one with different sowing dates and hybrids (Hyola 61 and Hyola 432) and another with doses of 10, 20, 40, 80, 160kg ha-1 of N, applied in top dressing. They were conducted in Passo Fundo and Coxilha, RS, Brazil, in 2011 and 2014, respectively.The evaluated variables were: area index of reproductive structures, interception efficiency and extinction coefficient of these structures for PAR. PAR interception increased by increasing the reproductive structures volume. Interception efficiency of PAR by reproductive structures ranged from 45 to 80%. It was higher in the Hyola 61 hybrid and at the highest dose of N. The extinction coefficient of reproductive structures for PAR was 0.44 in non-limiting doses of N.